2004
DOI: 10.1002/j.0022-0337.2004.68.8.tb03834.x
|View full text |Cite
|
Sign up to set email alerts
|

Predoctoral Dental School Curriculum for Catastrophe Preparedness

Abstract: Preparing for catastrophic events, both human-made and natural, is in the national interest and has become a priority since catastrophic events in Oklahoma City, Washington, DC, and New York City. Dentists are a large source of non-physician health manpower that could contribute to the public welfare during catastrophic events that require additional public health human resources. Dentists, by virtue of their education, understand biomedical concepts and have patient care skills that can be directly applied du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 5 publications
1
42
0
1
Order By: Relevance
“…This resulted in 79 full-text articles; 4 full-text articles could not be retrieved, and 37 did not meet the inclusion criteria, leaving 38 references for analysis ( Figure 1). 2,4,5,[14][15][16] Twenty-seven references were peer-review articles, 2,5,[14][15][16]21,22,24,[27][28][29][31][32][33][34]36,37,[38][39][40]42,43,45,[48][49][50][51] one was a book chapter, 4 4 were reports, 25,26,41,44 and 6 were documents available on the websites of relevant organizations. 20,23,30,35,46,47 Articles were referred to a single sector references.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This resulted in 79 full-text articles; 4 full-text articles could not be retrieved, and 37 did not meet the inclusion criteria, leaving 38 references for analysis ( Figure 1). 2,4,5,[14][15][16] Twenty-seven references were peer-review articles, 2,5,[14][15][16]21,22,24,[27][28][29][31][32][33][34]36,37,[38][39][40]42,43,45,[48][49][50][51] one was a book chapter, 4 4 were reports, 25,26,41,44 and 6 were documents available on the websites of relevant organizations. 20,23,30,35,46,47 Articles were referred to a single sector references.…”
Section: Resultsmentioning
confidence: 99%
“…27 Only 5 (13%) of the articles described subcompetencies and 5 (13%) defined performance objectives. 15,16,34,40,46 Thirty-one articles (81%) clearly described the method adopted to define competencies. A total of 19 (50%) used consensus-building, 5,15,16,20,[22][23][24][25][26]28,29,[31][32][33]40,41,43,46 3 articles identified competencies by survey or self-assessment questionnaires, 27,37,48 6 reported competencies based solely on a literature review, 2,14,39,42,49,50 and 4 reported or adapted competencies originally described by previously published articles.…”
Section: Resultsmentioning
confidence: 99%
“…Further, graduates of these hospital-based programs often continue to have hospital practices or affiliations. These competencies are based on the recognition that the knowledge and skills of an average dental graduate may be utilized by the public healthcare system in times of crisis [33]. However, a revised curriculum with the inclusion of handling of medical emergencies needs to be enforced in all dental teaching institutions.…”
Section: Existing Curriculum In Dental Institutionsmentioning
confidence: 99%
“…Strategies to achieve curriculum objectives include (10) : integrate cognitive information that is already part of the curriculum, Increase curriculum emphasis on public health, epidemiology, and health promotion, use exercises to facilitate application of knowledge of circumstances characteristic of manmade and natural catastrophic events and public health emergencies, use case studies, drills, and dramatizations using multimedia (such as videotaped scenarios) to simulate potential catastrophic events and to effectively study the circumstances surrounding past events, organize catastrophe drills in a manner that provides evaluation and direct feedback, introduce new units to provide advanced training for volunteers who want to be equipped for service at the frontline after an event.…”
Section: Planning Specific Classroom or Other Learning Experiences Thmentioning
confidence: 99%